New records of rare species in the Mediterranean Sea (November 2020). - Bo, M.; Al Mabruk, S.A.A.; Balisteri, P.; Bariche, M.; Batjakas, I.E; Betti, F.; Bilan, M.; Canese, S.; Cattaneo-Vietti, R.; Corsinifoka, M.; Crocetta, F.; Deidun, A.; et al. (Mediterranean Marine Science, 2020)
This Collective Article presents information about 21 taxa belonging to seven Phyla (one Ochrophyta, one Porifera, three Cnidaria, two Arthropoda, three Mollusca, one Echinodermata, and ten Chordata) and extending from the western Mediterranean Sea to the Levantine Sea. The new records were reported from nine countries as follows: Spain: first records of three deep-sea species from the Blanes Canyon along the Catalan margin, namely the gorgonian Placogorgia coronata, the bivalve Acesta excavata, and the Azores rockling Gaidropsarus granti; Italy: first record of the mesopsammic nudibranch Embletonia pulchra from Ligurianshallow-waters; first record of the deep-sea carnivorous sponge Lycopodina hypogea from the north-central Tyrrhenian Sea, living in dense clusters over dead black corals; new records of the Portuguese man o’ war Physalia physalis from Sardinian and Sicilian waters; first Italian record of the large asteroid Coronaster briareus from the Ionian Sea; first record of the white grouper Epinephelus aeneus in the northernmost point of the Adriatic Sea; Croatia: first record of the gastropod Haliotis mykonosensis for the Adriatic Sea; Malta: new sightings of Physalia physalis from Maltese waters; Libya: first record of the sand crab Albunea carabus from two localities along the Libyan coast; Greece: first records of the deep-sea black coral Parantipathes larix from the eastern Mediterranean Sea; first verified record of the agujon needlefish Tylosurus imperialis in the Hellenic Ionian Sea; first confirmed record of the brown algae Treptacantha squarrosa in the eastern Mediterranean Sea; new records of three deep-sea fishspecies from the Aegean Sea, namely the bluntnose sixgill shark Hexanchus griseus, the Atlantic pomfret Brama brama, and the rudderfish Centrolophus niger; new record of the tripletail Lobotes surinamensis from Lesvos Island; new record of the shrimp Brachycarpus biunguiculatus from the gut content of the non-indigenous lionfish Pterois miles; Turkey: new record of the imperial blackfish Schedophilus ovalis from Turkish waters; Lebanon: first record of the slender sunfish Ranzania laevis, stranded along the Lebanese coast; Israel: new record, after about 60 years from the last catch, of the spotted dragonet Callionymus maculatus.